2019
DOI: 10.3389/fneur.2019.00343
|View full text |Cite
|
Sign up to set email alerts
|

Pre-injury Comorbidities Are Associated With Functional Impairment and Post-concussive Symptoms at 3- and 6-Months After Mild Traumatic Brain Injury: A TRACK-TBI Study

Abstract: Introduction: Over 70% of traumatic brain injuries (TBI) are classified as mild (mTBI), which present heterogeneously. Associations between pre-injury comorbidities and outcomes are not well-understood, and understanding their status as risk factors may improve mTBI management and prognostication. Methods: mTBI subjects (GCS 13–15) from TRACK-TBI Pilot completing 3- and 6-month functional [Glasgow Outcome Scale-Extended (GOSE)] and post-concussive outcomes [Acute Concussion E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…Like other acute mTBI studies in adults presenting to the ED, we observed a high prevalence of previously identified risk factors for the development of PCS, including comorbid mental health conditions, prior concussions, and alcohol and drug use. [32][33][34] The largest prior study was a prospective, multicenter longitudinal study, known symptoms at 3 and months. 33,34 Preinjury psychiatric history and preinjury headache/migraine symptoms, both prevalent in our cohort, were predictive of worse functional and postconcussive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Like other acute mTBI studies in adults presenting to the ED, we observed a high prevalence of previously identified risk factors for the development of PCS, including comorbid mental health conditions, prior concussions, and alcohol and drug use. [32][33][34] The largest prior study was a prospective, multicenter longitudinal study, known symptoms at 3 and months. 33,34 Preinjury psychiatric history and preinjury headache/migraine symptoms, both prevalent in our cohort, were predictive of worse functional and postconcussive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This may simply be explained by the relative ease with which patients can return to part-time rather than full-time work. RTW at three months predicted RTW at six 46 our data suggests that patients should be screened at or prior to three months for risk of delayed RTW, and at-risk patients should be directed to vocational rehabilitation services as quickly as possible. Finally, it is worth noting that history of illicit substance use was a predictor for inability to RTW at six months.…”
Section: Discussionmentioning
confidence: 74%
“…Women seem to have a higher incidence of sleep disorders after one incidence of mild TBI; however, with recurrent injuries, both males and females report sleep disorders equally (89). Pre-injury co-morbidities, such as headache or migraine, seem to increase risk of post-injury sleep disorders in adults (90). Some of these co-morbidities may be expressed in sexually dimorphic patterns, and this likely impacts the sleep disorder incidence post-TBI based on sex.…”
Section: Sleep Disordersmentioning
confidence: 99%